Evaluasi dan Perbaikan Desain Antarmuka Pengguna Website RSU Siaga Medika Menggunakan Metode Human-Centered Design - Dewi, Talitha Yulistya; Septiadi, Abednego Dwi (Universitas Multi Data Palembang, 2023)
Currently, information needs are required by various agencies. In achieving a good information system, it takes the support of technology as a data processing tool. Internet with a system that produces websites can be an alternative to obtain sources of information that can be accessed anywhere and anytime. Agencies in the health sector implement the use of websites as an effective and efficient dissemination of Information Services. The performance of an agency website is determined by the services provided to users it shows the need for interface evaluation to support the development of service processes to meet user needs. In this study the evaluation is done by the method of Human-Centered Design through 4 stages, specify the context of use, specify user and organizational requirements, produce design solutions, and evaluate designs against user requirements. Darta retrieval based on the results of observations, interviews and questionnaires to stakeholders and users of the RSU Siaga Medika website in Banyumas. The results of the evaluation of this interface in the form of recommendations for the design of solutions that can be used to improve the website interface of RSU Siaga Medika Banyumas. Keywords: evaluation, Human-Centered Design, interface improvement